Horses of a Shared Colour: Interpreting Class and Identity in Turn-of-the-Century Vancouver - Nelles, H. V. (Labour / Le Travail, 1997)
The article reviews several books including "Red Flags and Red Tape: The Making of a Labour Bureaucracy," by Mark Leier and "Making Vancouver: Class, Status and Social Boundaries," by Robert A. J. McDonald.
Keywords: BOOKS – Reviews; LEIER; Mark; MAKING Vancouver: Class; Status & Social Boundaries (Book); MCDONALD; Robert A. J.; 1944-; Nonfiction; RED Flags & Red Tape: The Making of a Labour Bureaucracy (Book)